2014
DOI: 10.1021/jp503865y
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Proton Transfer and Isomerization in a Hydrogen-Bonded Aromatic Azo Compound: A CASPT2//CASSCF Study

Abstract: Intramolecularly hydrogen-bonded aromatic azo compound 1-cyclopropyldiazo-2-naphthol (CPDNO) exhibits complicated excited-state behaviors, e.g., wavelength-dependent photoinduced proton transfer and photoproducts. Its photochemistry differs from that of common aromatic azo compounds in which cis-trans photoisomerization is dominant. To rationalize the intriguing photochemistry of CPDNO at the atomic level, we have in this work employed the complete active space self-consistent field (CASSCF) and its second-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…It can be found that Wiberg bond index of the N2⋅⋅⋅H7 hydrogen bond is more than twice as large in the 1 ππ* state than in the S 0 state; whereas the counterpart in the 1 n π* state is rather smaller. This hydrogen‐bond feature of augmenting in the 1 ππ* state but weakening in the 1 n π* state could hold true for similar systems 34. 7476…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…It can be found that Wiberg bond index of the N2⋅⋅⋅H7 hydrogen bond is more than twice as large in the 1 ππ* state than in the S 0 state; whereas the counterpart in the 1 n π* state is rather smaller. This hydrogen‐bond feature of augmenting in the 1 ππ* state but weakening in the 1 n π* state could hold true for similar systems 34. 7476…”
Section: Resultsmentioning
confidence: 84%
“…17 These applications are heavily interrelated to thermal and photoinduced isomerizations of the azo group 1820. To design and synthesize new azobenzene compounds with better performance, much experimental and theoretical effort has been dedicated in previous years to understanding the isomerization mechanisms of azobenzene and its variants at atomistic level 2134…”
Section: Introductionmentioning
confidence: 99%
“…More in detail, starting from the structures reported in Ref. , we have focused on the description of the relaxed minimum energy proton‐transfer profile occurring along the 1 ππ* PES. Using the optimized geometries reported in Ref.…”
Section: Density Based Indexes and Computational Approachesmentioning
confidence: 99%
“…Using the optimized geometries reported in Ref. , single point calculations were performed at the CASPT2 level of theory. Analogously to what has been done in Ref.…”
Section: Density Based Indexes and Computational Approachesmentioning
confidence: 99%
See 1 more Smart Citation